The dramaturgy of prison on the scene: a theatrical experiment at the Lemos Brito Penitentiary, in Rio de Janeiro (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Theatre in Prison: The Dramaturgy of Prison as a Theatrical Setting is a research project that developed out of the experimentation of the devising of a play about the experience of prison and featured prisoners from Lemos Brito Penitentiary, in Rio de Janeiro as actors.
Keywords: Theatre Education; Prison; Dramaturgy